A Review on Proton Pump Inhibitor for The Treatment of Peptic Ulcer - Saini, Priyanka; Sharma, Anu; Chhimwal, Jyoti; Kabra, Mahaveer; Singh, Sanjay (Asian Journal of Pharmaceutical Research and Development, 2013)
Ulcers are sores or open wounds that occur on the skin or along the lining of the digestive tract due to loss of tissue. Peptic ulcers are craters or open sores in the lining of the upper gastro intestinal tract. Occurs due to imbalance between defenses and aggressive factors. Proton-pump inhibitors (PPIs) are a group of drugs whose main action is a pronounced and longlasting reduction of gastric acid production. it act by irreversibly blocking the hydrogen/potassium adenosine triphosphatase enzyme system (the H + /K+ ATPase, or more commonly gastric proton pump) of the gastric parietal cells. The proton pump is the terminal stage in gastric acid secretion, being directly responsible for secreting H + ions into the gastric lumen, making it an ideal target for inhibiting acid secretion.